DINAMIKA PSIKOLOGIS PERILAKU KORUP KAUM ELIT POLITIK PEREMPUAN DAN UPAYA DAKWAH ISLAMIAH - Hasyim Hasanah (Yinyang: Jurnal Studi Islam Gender dan Anak, 2012)
Abstract: The main focus of this paper is to explore and analyze the motive and processes of elite women who commit bribery and corruption, analyzing the psychological impact of bribery and corruption of women, and mapping psychological points in finding propaganda strategy to overcome the corrupt behavior of the elite women. The method used in this paper is a qualitative descriptive phenomenological approach. The findings of this paper suggest that the elite women doing a lot of graft and corruption triggered by personal motives consumptive style which are very high. The process that is used to meet the expectation is to manipulate some administration financial documents such as marking-up the budget, distribute aspirations funds administration without valid proof. Psychological impact of this behavior that then arises is the rising level of stress, tending to become emotional and depressed. One effort that can be done to reduce the psychological impact of this behavior is by irsyad dakwah (good propaganda), i.e. the personal approach of the Islamic propaganda activities that involve more psychological aspects such as submission process and internalize the teachings of Islam, recognition, understanding, provide assistance, and resolve psychological problems. Kata Kunci: perilaku korup, elit perempuan, dan dakwah Islam.